A new perspective on binaural integration using response time methodology: super capacity revealed in conditions of binaural masking release - Lentz, Jennifer J.; He, Yuan; Townsend, James T. (Frontiers in Human Neuroscience, 2014)
This study applied reaction-time based methods to assess the workload capacity of binaural integration by comparing reaction time distributions for monaural and binaural tone-in-noise detection tasks. In the diotic contexts, an identical tone + noise stimulus was presented to each ear. In the dichotic contexts, an identical noise was presented to each ear, but the tone was presented to one of the ears 180o out of phase with respect to the other ear. Accuracy-based measurements have demonstrated a much lower signal detection threshold for the dichotic versus the diotic conditions, but accuracy-based techniques do not allow for assessment of system dynamics or resource allocation across time. Further, reaction times allow comparisons between these conditions at the same signal-to-noise ratio. Here, we apply a reaction-time based capacity coefficient, which provides an index of workload efficiency and quantifies the resource allocations for single ear versus two ear presentations. We demonstrate that the release from masking generated by the addition of an identical stimulus to one ear is limited-to-unlimited capacity (efficiency typically less than 1), consistent with less gain than would be expected by probability summation. However, the dichotic presentation leads to a significant increase in workload capacity (increased efficiency) – most specifically at lower signal-to-noise ratios. These experimental results provide further evidence that configural processing plays a critical role in binaural masking release, and that these mechanisms may operate more strongly when the signal stimulus is difficult to detect, albeit still with nearly 100% accuracy.